Changes in daytime sleepiness, quality of life, and objective sleep patterns in seasonal allergic rhinitis: a controlled clinical trial - Stuck, Boris; Johnson, Julia; Hagner, Anna Eva; Klimek, Ludger; Verse, Thomas; Hörmann, Karl; Maurer, Joachim T. (The journal of allergy and clinical immunology, 2004)
Background - It has long been assumed that allergic rhinitis leads to daytime sleepiness and a deterioration of nocturnal sleep, yet systematic studies have only been rarely conducted in this field. - Objective - The aim of the present study was to investigate the effects of seasonal allergic rhinitis on subjective and objective sleep patterns, quality of life, and daytime sleepiness in otherwise healthy subjects in comparison with nonallergic volunteers. - Methods - Twenty-five patients with seasonal allergic rhinitis and 25 healthy volunteers were enrolled in this prospective, controlled clinical trial. Daytime sleepiness and quality of life were assessed with the help of questionnaires (Epworth Sleepiness Scale, SF-36); 2 consecutive nights of fully attended polysomnography were performed before and during the pollen season of 2002. - Results - Statistically significant differences between groups were found in respect to changes in daytime sleepiness and selected parameters of quality of life. Impairment of daytime sleepiness and quality of life were related to the severity of the disease. Statistically significant differences were also found for selected parameters of the sleep studies, although the changes were only minimal, and all values were within normal ranges. - Conclusion - Seasonal allergic rhinitis leads to increased daytime sleepiness, as well as to an impairment of quality of life, depending on the severity of the disease. Objective measurements revealed a statistically significant influence of seasonal allergic rhinitis on selected sleep parameters, but changes were not of clinical relevance. Daytime sleepiness seems to be related to the condition itself rather than to an impairment of nocturnal sleep.
Gesehen am 11.03.2022